Reformasi Birokrasi dan Perubahan Perilaku Birokrat - Nurul Hidayah (Jurnal Transformasi Administrasi, 2014)
Community satisfaction can be a benchmark for the work of bureaucrats as the bearer of the mandate of Bureaucratic Reform. Therefore, it is only natural that the expectation for the realization of Bureaucratic Reform on the state's commitment stated in the 2010-1014 Bureaucratic Reformation Design is so great. However, what happened and felt until the first period of the agenda would end was that the Bureaucratic Reformation had not been able to change the face of our bureaucracy, which until now was still chaotic if it did not want to be said to fail.